2020
DOI: 10.1080/07399332.2020.1829626
|View full text |Cite
|
Sign up to set email alerts
|

Living in fear: The relationship between fear of COVID-19, distress, health, and marital satisfaction among Israeli women

Abstract: After the COVID-19 virus was officially declared a pandemic on March 11, 2020, the Israeli government adopted lockdown restrictions to limit its spread. The purpose of the present article is to examine the impact of this disturbing environment on Israeli women. Specifically, we examined whether fear of the virus would impact the women's distress symptoms, selfrated health (SRH), and marital satisfaction. A total of 130 Israeli married women with children completed the survey during the lockdown restrictions pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 70 publications
(113 reference statements)
3
37
0
3
Order By: Relevance
“…Not only that this study provides information regarding the families with lower SES, which is considered a risk group that received less attention during this situation (Holmes et al, 2020), but it also suggests that women's satisfaction is more strongly linked to stress, although they also can find some benefits in this situation. We know that women are uniquely influenced by the pandemic and more exposed to stress and negative mental health (Reizer et al, 2020) but this study suggests that they are not necessarily more prone to dips in satisfaction. However, their satisfaction is impacted by both their levels of stress and by their partner's level of stress.…”
Section: Practical Contributionsmentioning
confidence: 69%
See 1 more Smart Citation
“…Not only that this study provides information regarding the families with lower SES, which is considered a risk group that received less attention during this situation (Holmes et al, 2020), but it also suggests that women's satisfaction is more strongly linked to stress, although they also can find some benefits in this situation. We know that women are uniquely influenced by the pandemic and more exposed to stress and negative mental health (Reizer et al, 2020) but this study suggests that they are not necessarily more prone to dips in satisfaction. However, their satisfaction is impacted by both their levels of stress and by their partner's level of stress.…”
Section: Practical Contributionsmentioning
confidence: 69%
“…Past research showed that significant negative life events, such as wars and medical crises, exacerbate preexisting levels of stress and might lead to higher chances of relational dissolution (Prime et al, 2020). We also know that previous studies linked the stressors associated with the Covid-19 pandemic and the lockdown period, such as social isolation, financial strain or fear of Covid-19, with decreased marital satisfaction (Balzarini et al, 2020;Reizer et al, 2020;Schmid et al, 2021). Building from the first two models and from the existing empirical evidence, we can assume that the levels of stress in the context of the Coronavirus pandemic and lockdown would be associated with lower levels of relational satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…It is logical for participants to use emotional (e.g., concerns about health, especially for one's family and one's financial situation) in conjunction with practical coping strategies (e.g., attempts to protect themselves as well as their family). As mentioned before, the beginning of the pandemic was characterized by a general sense of confusion, resulting from the dramatic changes required to cope with the virus (Reizer et al, 2020). At that point, the media was saturated with information describing individual hardships, the extremely high infection rate, and the relatively high mortality.…”
Section: Gendermentioning
confidence: 99%
“…In addition to the aforementioned social and behavioral reasons, the role of emerging and reemerging infectious diseases, such as COVID-19, on marital con ict is not insigni cant. Recent research also illustrates that the nature and various indirect consequences of the COVID-19 pandemic results in marital con ict (2) (8). In all aspects, there are controversies in risks for marital con ict, for instance, marriage duration, and age-at-marriage might not be strong enough to predict marital con ict (9).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, marriage is a social construct in the form of a formal union of a man and a woman, typically recognized by law, by which they become husband and wife on a range of issues (1). Inherently, it is a complex phenomenon that the risks for marital instability are ubiquitous including social upheavals, stay home order due to Coronavirus Disease 2019 (COVID-19) (2).…”
Section: Introductionmentioning
confidence: 99%